Biometric indices of two sugarcane varieties - Machado, Eduardo Caruso; Pereira, Antonio Roberto; Fahl, Joel Irineu; Arruda, Hermano Vaz; Cione, José (Pesquisa Agropecuaria Brasileira, 2014)
The biometrics characteristics of the sugarcane varieties NA 56-79 and CB 41-14 revealed similar growth patterns during one year cycle. Increase in phytomass as well as in leaf area with time after planting had a sigmoid shape and were independent of variety. Leaf Area Index increased up to 3.7 about 300 days after planting (d.a.p.) becoming constant afterward. The leaves represented, initially, over 70% of the total dry mass; such proportion decreased to 9% in the final stages of growth (400 d.a.p.). Both varieties had an overproduction of stalks in the closing-in stages of the crop with a peak attained about 125 d.a.p. Later, due mainly to mutual shading and competition among stalk, there was a natural reduction of 50% in the number of stalks/m2. Crop Growth Rate and Net Assimilation Rate peaked about 300 d.a.p. with, respectively, 25 and 7 g. m-2 . d-1.